2017
DOI: 10.1126/sciadv.1603259
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 is a critical regulator of FGF23 homeostasis

Abstract: Pharmacological inhibition of PAI-1 augments proteolytic clearance of FGF23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
(77 reference statements)
0
24
1
Order By: Relevance
“…PAI‐1 may enhance FGF23 levels by inhibiting furin‐like proteases . In line with this, plasminogen activators (PAs) directly cleave FGF23 .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 84%
See 2 more Smart Citations
“…PAI‐1 may enhance FGF23 levels by inhibiting furin‐like proteases . In line with this, plasminogen activators (PAs) directly cleave FGF23 .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 84%
“…Impaired renal function in CKD or acute kidney injury (AKI) is a major stimulus of FGF23 production . In animal models of AKI, FGF23 rises within hours and before onset of hyperphosphataemia .…”
Section: Fgf23 Regulation: Insights From Rare Disorders and Renal Dismentioning
confidence: 99%
See 1 more Smart Citation
“…and a series of analogues with improved pharmacological and toxicological properties, including TM5509 and TM5614 44,45 . A number of preclinical studies have demonstrated that this series of compounds is capable of affecting a number of metabolic, fibrotic, aging-related disorders, and hematopoietic regeneration [46][47][48][49][50] . In this study, we provide the first evidence that inhibition of iPAI-1 can be of therapeutic benefit in the treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain is essential for interaction with and activating the FGFR-Klotho complex [16]. Between the N- and C-terminal domains is a proteolytic site (176 RXXR 179), and FGF23 is inactivated by subtilisin-like proprotein convertase and plasminogen activators, resulting in two inactive N- and active C-terminal fragments [10, 21, 23, 22, 43, 72, 90, 102]. The C-terminal fragment can competitively interfere the formation of intact FGF23/αKlotho/FGFR complex, thus acting as a natural FGF23 antagonist [34].…”
Section: Fgf23 Fgfrs αKlotho Expression and Regulationmentioning
confidence: 99%